Synoptic drivers of 400 years of summer temperature and precipitation variability on Mt. Olympus, Greece - Klesse, Stefan; Ziehmer, Malin; Rousakis, Georgios; Trouet, Valerie; Frank, David (Climate Dynamics, 2015)
ISSN:0930-7575 ISSN:1432-0894